Anode for lithium secondary battery, method for producing anode for lithium secondary battery, and lithium secondary battery including anode

By adopting a double-layer negative electrode material structure in lithium-ion batteries and using the combination of high silicon oxide and carbon-based materials, the electrode degradation problem caused by volume expansion during charging and discharging of silicon-based materials is solved, and the capacity and life characteristics of the battery are improved.

JP7625331B2Active Publication Date: 2025-02-03LG ENERGY SOLUTION LTD
View PDF 8 Cites 0 Cited by

Patent Information

Application Number
JP2023537372
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2022-05-31
Filing Date
2022-07-08
Publication Date
2025-02-03
Estimated Expiration
2042-07-08

AI Technical Summary

Technical Problem

In the prior art, in lithium-ion batteries using silicon-based negative electrode materials, there are problems such as electrode surface degradation and reduced life characteristics due to volume expansion, especially during the charge and discharge cycle, the high capacity characteristics of the silicon-based material cannot be effectively utilized.

Method used

A double-layer negative electrode material structure is adopted, wherein the first layer is a mixture containing high silicon oxide (SIOX) and the second layer is a carbon-based or silicon-based material. By adjusting the proportion and composition of the two layers of materials, a buffer layer is formed to limit the volume changes in the previous lithiation process and optimize the capacity and life characteristics of the electrode.

Benefits of technology

It effectively suppresses the degradation of the electrode surface during charging and discharging, improves the capacity and life characteristics of lithium-ion batteries, and achieves high capacity and fast charging and discharging performance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007625331000003
    Figure 0007625331000003
  • Figure 0007625331000004
    Figure 0007625331000004
  • Figure 0007625331000005
    Figure 0007625331000005
Patent Text Reader

Abstract

The present application relates to a negative electrode for a lithium secondary battery, a method for producing a negative electrode for a lithium secondary battery, and a lithium secondary battery including the negative electrode.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] This application claims the benefit of the filing dates of Korean Patent Application No. 10-2021-0090580 filed with the Korean Intellectual Property Office on July 9, 2021, Korean Patent Application No. 10-2021-0189600 filed with the Korean Intellectual Property Office on December 28, 2021, and Korean Patent Application No. 10-2022-0066756 filed with the Korean Intellectual Property Office on May 31, 2022, the entire contents of which are incorporated herein by reference.

[0002] The present application relates to a negative electrode for a lithium secondary battery, a method for producing a negative electrode for a lithium secondary battery, and a lithium secondary battery including the negative electrode. [Background technology]

[0003] The rapid increase in the use of fossil fuels has led to an increased demand for alternative and clean energy, and one of the most actively researched fields in this area is power generation and storage using electrochemical reactions.

[0004] At present, secondary batteries are a typical example of electrochemical elements that utilize such electrochemical energy, and the range of their use is tending to expand more and more.

[0005] As technological development and demand for mobile devices increases, the demand for secondary batteries as energy sources is rapidly increasing. Among such secondary batteries, lithium secondary batteries, which have high energy density and voltage, long cycle life, and low self-discharge rate, have been commercialized and widely used. In addition, research into a method for manufacturing a high-density electrode with a higher energy density per unit volume as an electrode for such high-capacity lithium secondary batteries is being actively conducted.

[0006] In general, a secondary battery is composed of a positive electrode, a negative electrode, an electrolyte, and a separator. The negative electrode includes a negative electrode active material that inserts and removes lithium ions from the positive electrode. Silicon-based particles having a large discharge capacity can be used as the negative electrode active material.

[0007] In particular, in recent years, in response to the demand for high-density energy batteries, active research has been conducted into methods of increasing capacity by using silicon-based compounds such as Si / C and SiOx, which have a capacity 10 times larger than that of graphite-based materials, as negative electrode active materials. However, in the case of silicon-based compounds, which are high-capacity materials, they are materials with a large capacity compared to conventionally used graphite and have excellent capacity characteristics, but their volume expands rapidly during charging, cutting off the conductive path and reducing battery characteristics, resulting in a drop in capacity from the beginning. In addition, when silicon-based negative electrodes undergo repeated charge and discharge cycles, lithium ions are not uniformly charged in the depth direction of the negative electrode, and reactions proceed on the surface, accelerating surface degradation, so performance needs to be improved in terms of battery cycles.

[0008] In order to solve the above problems when using silicon-based compounds as negative electrode active materials, various methods are being discussed, such as a method of adjusting the driving potential, a method of further coating a thin film on the active material layer, a method of adjusting the particle size of the silicon-based compound, and the development of a binder that suppresses the volume expansion of the silicon-based compound to prevent the conductive path from being broken. In addition, research is also being conducted to limit the usage ratio of silicon-based active materials used during initial charging and discharging through a method of pre-lithiating the silicon-based active material layer, to provide a role as a reservoir, and to complement the life characteristics of silicon-based negative electrodes.

[0009] However, in the case of the above method, since it may deteriorate the performance of the battery, there is a limit to its application, and there is still a limit to the commercialization of negative electrode batteries having a high content of silicon-based compounds. As the ratio of silicon-based active material contained in the silicon-based active material layer increases, pre-lithiation is concentrated on the surface of the negative electrode, which causes damage to the silicon-based active material on the surface side, and non-uniform pre-lithiation occurs, resulting in problems in improving the life characteristics.

[0010] Therefore, even when a silicon-based compound is used as an active material, there is a need for research into lithium secondary batteries that can prevent the degradation of the electrode surface during charge and discharge cycles, and that can improve the uniformity of the pre-lithiation process and provide optimally excellent results. [Prior art documents] [Patent documents]

[0011] [Patent Document 1] JP 2009-080971 A Summary of the Invention [Problem to be solved by the invention]

[0012] The present application is capable of maximizing the capacity characteristics, which is the main purpose of using a silicon-based active material, while preventing the existing problem of electrode surface degradation during charge and discharge cycles. Furthermore, as a result of research into a method for improving the uniformity of pre-lithiation and improving both capacity and life characteristics, it has been confirmed that the above problem can be solved by adjusting the pre-lithiation ratio within a specific range.

[0013] Thus, the present invention relates to a negative electrode for a lithium secondary battery that satisfies the range of formula 1, a method for producing a negative electrode for a lithium secondary battery, and a lithium secondary battery including the negative electrode. [Means for solving the problem]

[0014] One embodiment of the present specification is a negative electrode for a lithium secondary battery including: a negative electrode current collector layer; a first negative electrode active material layer provided on one or both surfaces of the negative electrode current collector layer; and a second negative electrode active material layer provided on a surface opposite to the surface of the first negative electrode active material layer in contact with the negative electrode current collector layer. The first negative electrode active material layer includes a first negative electrode active material layer composition containing a first negative electrode active material. The second negative electrode active material layer includes a second negative electrode active material layer composition containing a second negative electrode active material. The first negative electrode active material layer includes one or more selected from the group consisting of SiOx (x = 0) and SiOx (0 < x < 2), and contains 95 parts by weight or more of SiOx (x = 0) based on 100 parts by weight of the first negative electrode active material. The second negative electrode active material includes a mixture of one or more selected from the group consisting of a carbon-based active material, a silicon-based active material, a metal-based active material capable of alloying with lithium, and a lithium-containing nitride. The silicon-based active material is 1 part by weight or more and 100 parts by weight or less based on 100 parts by weight of the second negative electrode active material. The second negative electrode active material layer satisfies the following formula 1. A negative electrode for a lithium secondary battery is provided. [Formula 1] 0.5 ≦ B / A ≦ 2 In Formula 1 above, A is the discharge capacity of the second negative electrode active material layer, B means the capacity of pre-lithiated lithium.

[0015] Also, in one embodiment of the present application, the first negative electrode active material layer may be formed on a partial surface or the entire surface of the negative electrode current collector layer, and the second negative electrode active material layer may be formed on a partial surface or the entire surface of the first negative electrode active material layer.

[0016] In yet another embodiment, a step of preparing a negative electrode current collector layer; a step of forming a first negative electrode active material layer by applying a first negative electrode active material layer composition on one or both surfaces of the negative electrode current collector layer; and a step of forming a second negative electrode active material layer by applying a second negative electrode active material layer composition on the opposite surface of the first negative electrode active material layer that contacts the negative electrode current collector layer; A method for manufacturing a negative electrode for a lithium secondary battery, wherein the first negative electrode active material includes at least one selected from the group consisting of SiOx (x = 0) and SiOx (0 <x <2), and based on 100 parts by weight of the first negative electrode active material, it contains 95 parts by weight or more of SiOx (x = 0), and the second negative electrode active material includes one or more mixtures selected from the group consisting of a carbon-based active material, a silicon-based active material, a metal-based active material capable of alloying with lithium, and a lithium-containing nitride, and the silicon-based active material is 1 part by weight or more and 100 parts by weight or less based on 100 parts by weight of the second negative electrode active material, and the second negative electrode active material layer satisfies the above formula 1, and provides a method for manufacturing a negative electrode for a lithium secondary battery.

[0017] Also, in one embodiment of the present application, the first negative electrode active material layer may be formed on a partial surface or the entire surface of the negative electrode current collector layer, and the second negative electrode active material layer may be formed on a partial surface or the entire surface of the first negative electrode active material layer.

[0018] Finally, a positive electrode; a negative electrode for a lithium secondary battery according to the present application; a separator provided between the positive electrode and the negative electrode; and an electrolyte; A lithium secondary battery is provided.

Effects of the Invention

[0019] In the case of the negative electrode for a lithium secondary battery according to an embodiment of the present invention, it has a double-layer active material layer composed of a first negative electrode active material layer and a second negative electrode active material layer. In particular, the first negative electrode active material contained in the first negative electrode active material layer contains at least one selected from the group consisting of SiOx (x = 0) and SiOx (0 < x < 2), and contains 95 parts by weight or more of the SiOx (x = 0) based on 100 parts by weight of the first negative electrode active material. The second negative electrode active material contained in the second negative electrode active material layer contains at least one mixture selected from the group consisting of a carbon-based active material, a silicon-based active material, a metal-based active material capable of alloying with lithium, and a lithium-containing nitride.

[0020] The negative electrode for a lithium secondary battery according to the present application has a double-layer active material layer having the specific composition and content as described above. In particular, the first negative electrode active material layer contains a high content of SiOx (x = 0), and can directly have advantages favorable for high capacity, high density, and rapid charging. Further, the second negative electrode active material layer contains a silicon-based and carbon-based active material, etc., which can prevent the degradation of the electrode surface during the progress of charge and discharge cycles, and can also improve the uniformity during pre-lithiation.

[0021] Furthermore, the negative electrode for a lithium secondary battery according to the present application is characterized in that the ratio of pre-lithiation is adjusted to a specific range according to the discharge capacity of the second negative electrode active material layer composition. That is, the negative electrode for a lithium secondary battery according to the present application adjusts the capacity of lithium imparted to pre-lithiation to the range of Formula 1 with respect to the discharge capacity of the second active material layer containing a silicon-based active material. Thereby, it has a first negative electrode active material layer composition having high capacity characteristics, includes a second negative electrode active material layer composition for solving life characteristics, restricts the usage ratio of the silicon-based active material during initial charge and discharge, and imparts the role of a reservoir to optimize capacity characteristics and life characteristics, showing excellent effects.

[0022] In conclusion, the negative electrode for a lithium secondary battery according to the present application is characterized in that it is configured as a double layer in which a first negative electrode active material layer and a second negative electrode active material layer are applied with a specific composition and a specific pre-lithiation ratio in order to obtain the advantages of an electrode using a high content of Si particles in a single layer active material, while resolving the disadvantages of having such an electrode, such as the problem of surface degeneration, the problem of uniformity during pre-lithiation, and the problem of life characteristics. [Brief description of the drawings]

[0023] [Figure 1] FIG. 1 is a diagram showing a laminated structure of a negative electrode for a lithium secondary battery according to an embodiment of the present application. [Diagram 2] FIG. 1 is a diagram showing the RPT capacity maintenance rates according to examples and comparative examples of the present application. [Diagram 3] FIG. 1 is a diagram showing the RPT resistance increase rate according to the examples and comparative examples of the present application. [Figure 4] FIG. 1 is a diagram showing a laminated structure of a negative electrode for a lithium secondary battery according to an embodiment of the present application. [Diagram 5] 1 is a flow chart illustrating a wet on dry process according to one embodiment of the present application. [Figure 6] 1 is a flow chart illustrating a wet on wet process according to one embodiment of the present application. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0024] Before describing the present invention, some terms will first be defined.

[0025] In this specification, when a part is said to "comprise" a certain element, this means that it may further include other elements, rather than excluding other elements, unless specifically stated to the contrary.

[0026] In this specification, "p to q" means a range of "not less than p and not more than q".

[0027] In this specification, the "specific surface area" is measured by the BET method, and specifically, is calculated from the amount of nitrogen gas adsorption at liquid nitrogen temperature (77K) using a BELSORP-mino II manufactured by BEL Japan Co., Ltd. That is, in this application, the BET specific surface area can mean the specific surface area measured by the above-mentioned measurement method.

[0028] In this specification, "Dn" means particle size distribution, and refers to the particle size at the n% point of the cumulative particle number distribution according to particle size. That is, D50 is the particle size (average particle size, median particle size) at the 50% point of the cumulative particle number distribution according to particle size, D90 is the particle size at the 90% point of the cumulative particle number distribution according to particle size, and D10 is the particle size at the 10% point of the cumulative particle number distribution according to particle size. Meanwhile, the particle size distribution can be measured using a laser diffraction method. Specifically, the powder to be measured is dispersed in a dispersion medium, and then introduced into a commercially available laser diffraction particle size measuring device (e.g., Microtrac S3500) to measure the difference in the diffraction pattern according to the particle size when the particles pass through a laser beam, and the particle size distribution is calculated.

[0029] In this specification, when a polymer contains a certain monomer as a monomer unit, it means that the monomer is involved in a polymerization reaction and is contained as a repeating unit in the polymer. In this specification, when a polymer contains a monomer, this is interpreted in the same way as when a polymer contains a monomer as a monomer unit.

[0030] In this specification, the term "polymer" is understood to be used in a broad sense including copolymers, unless otherwise specified as a "homopolymer."

[0031] In this specification, the weight-average molecular weight (Mw) and the number-average molecular weight (Mn) are the polystyrene-equivalent molecular weights measured by gel permeation chromatography (GPC) using monodisperse polystyrene polymers (standard samples) of various degrees of polymerization commercially available for molecular weight measurement as standard substances. In this specification, the molecular weight means the weight-average molecular weight unless otherwise specified.

[0032] Hereinafter, a detailed description will be given with reference to the drawings so that those having ordinary knowledge in the technical field to which the present invention pertains can easily implement the present invention. However, the present invention may be embodied in various different forms and is not limited to the following description.

[0033] One embodiment of this specification is a negative electrode for a lithium secondary battery including a negative electrode current collector layer; a first negative electrode active material layer provided on one or both surfaces of the negative electrode current collector layer; and a second negative electrode active material layer provided on the surface opposite to the surface of the first negative electrode active material layer that contacts the negative electrode current collector layer, wherein the first negative electrode active material layer includes a first negative electrode active material layer composition containing a first negative electrode active material, the second negative electrode active material layer includes a second negative electrode active material layer composition containing a second negative electrode active material, the first negative electrode active material layer includes one or more selected from the group consisting of SiOx (x = 0) and SiOx (0 < x < 2), contains 95 parts by weight or more of SiOx (x = 0) based on 100 parts by weight of the first negative electrode active material, the second negative electrode active material includes a mixture of one or more selected from the group consisting of a carbon-based active material, a silicon-based active material, a metal-based active material capable of alloying with lithium, and a lithium-containing nitride, the silicon-based active material is 1 part by weight or more and 100 parts by weight or less based on 100 parts by weight of the second negative electrode active material, and the second negative electrode active material layer satisfies the following formula 1, and provides a negative electrode for a lithium secondary battery. [Formula 1] 0.5 ≦ B / A ≦ 2 In the above formula 1, A is the discharge capacity of the second negative electrode active material layer, B means the capacity of pre-lithiated lithium.

[0034] The negative electrode for a lithium secondary battery according to the present application uses a second negative electrode active material layer acting as a buffer layer to effectively use the first negative electrode active material contained in the first negative electrode active material layer, and has a feature that the second negative electrode active material layer satisfies the range of formula 1, and thus pre-lithiation proceeds without damaging the first negative electrode active material layer.

[0035] As an example, the second negative electrode active material layer of the present application can act as a buffer layer. An electrode containing a Si active material has superior capacity characteristics compared to an electrode containing a SiO or carbon-based active material. However, an electrode containing a Si active material has a tendency to concentrate deterioration of the surface of the negative electrode active material layer due to a rapid reaction with Li ions during charging and discharging. This also occurs during the pre-lithiation process in which lithium ions are pre-contained in the negative electrode active material layer. In the pre-lithiation process, the buffer layer is used to prevent direct contact between the Si-based electrode and lithium and to prevent surface deterioration. Therefore, the second negative electrode active material layer of the present invention has the characteristic of being able to play the same role and exhibit the same effect as the buffer layer in the pre-lithiation process. As a result, the battery has a first negative electrode active material layer composition having high capacity characteristics, and includes a second negative electrode active material layer composition to solve life characteristics. The usage ratio of the silicon-based active material during initial charging and discharging is limited, and the battery acts as a reservoir, optimizing capacity characteristics and life characteristics, thereby providing excellent effects.

[0036] FIG. 1 is a diagram showing a laminated structure of a negative electrode for a lithium secondary battery according to an embodiment of the present application. Specifically, a negative electrode for a lithium secondary battery 100 including a first negative electrode active material layer 20 and a second negative electrode active material layer 30 can be seen on one side of a negative electrode current collector layer 30. Although FIG. 1 shows that the first negative electrode active material layer is formed on one side, it may be formed on both sides of the negative electrode current collector layer. As described above, in one embodiment of the present application, the first negative electrode active material layer may be formed on the entire surface of the negative electrode current collector layer, and the second negative electrode active material layer may be formed on the entire surface of the first negative electrode active material layer.

[0037] FIG. 4 is a diagram showing a laminated structure of a negative electrode for a lithium secondary battery according to an embodiment of the present application. Specifically, as shown in FIG. 4, a first negative electrode active material layer 20 and a second negative electrode active material layer 30 can be formed on both sides of a negative electrode current collector layer 30. Also, the arrangement may be 10>20>30>20>10, and further, when the first negative electrode active material layer and the second negative electrode active material layer are sequentially laminated only on one side of the negative electrode current collector layer, they can be laminated regardless of the arrangement on the opposite side, such as 10>20>30>20, 10>20>30>10, 10>20>30>10>20, etc. It is preferable that both sides of the negative electrode current collector layer have the same composition, and specifically, the structure may be 10>20>30>20>10.

[0038] The negative electrode for a lithium secondary battery of the present invention will be described in more detail below.

[0039] In one embodiment of the present application, there is provided a negative electrode for a lithium secondary battery, comprising: a negative electrode current collector layer; a first negative electrode active material layer provided on one or both sides of the negative electrode current collector layer; and a second negative electrode active material layer provided on a side of the first negative electrode active material layer opposite to a side in contact with the negative electrode current collector layer.

[0040] In one embodiment of the present application, the negative electrode current collector layer generally has a thickness of 1 μm to 100 μm. Such a negative electrode current collector layer is not particularly limited as long as it does not induce chemical changes in the battery and has high conductivity, and for example, copper, stainless steel, aluminum, nickel, titanium, baked carbon, copper or stainless steel surface-treated with carbon, nickel, titanium, silver, etc., aluminum-cadmium alloy, etc. may be used. In addition, the binding force of the negative electrode active material can be strengthened by forming fine irregularities on the surface, and it can be used in various forms such as a film, sheet, foil, net, porous body, foam, nonwoven fabric, etc.

[0041] In one embodiment of the present application, the negative electrode current collector layer may have a thickness of 1 μm or more and 100 μm or less.

[0042] In one embodiment of the present application, there is provided a negative electrode for a lithium secondary battery, wherein the first negative electrode active material layer has a thickness of 10 μm or more and 200 μm or less, and the second negative electrode active material layer has a thickness of 10 μm or more and 100 μm or less.

[0043] However, the thickness can be changed in various ways depending on the type and application of the negative electrode used, and is not limited thereto.

[0044] In one embodiment of the present application, there is provided a negative electrode for a lithium secondary battery, in which the weight loading amount (a) of the first negative electrode active material layer composition is 1.5 times or more the weight loading amount (b) of the second negative electrode active material layer composition.

[0045] In another embodiment, the weight loading amount (a) of the first negative electrode active material layer composition may be in the range of 1.5 to 10 times, preferably 2.2 to 6 times, the weight loading amount (b) of the second negative electrode active material layer composition.

[0046] The weight loading amount may refer to the weight of a composition for forming a negative electrode active material layer, and specifically, the weight loading amount of a composition may have the same meaning as the loading amount of a slurry containing the composition.

[0047] In one embodiment of the present application, the weight loading (a) of the first negative electrode active material layer composition is 2 mg / cm 2 More than 5mg / cm 2 Less than 2.2 mg / cm, preferably 2.2 mg / cm 2 More than 4mg / cm 2 The following ranges may be satisfied:

[0048] In one embodiment of the present application, the weight loading (b) of the second negative electrode active material layer composition is 0.5 mg / cm 2 More than 1.5mg / cm 2 Less than 0.8 mg / cm, preferably 0.8 mg / cm 2 More than 1.3mg / cm 2 The following ranges may be satisfied:

[0049] By satisfying the above formula (1) for the first negative electrode active material layer composition and the second negative electrode active material layer composition, the ratio of the active materials contained in the first negative electrode active material layer and the second negative electrode active material layer can be adjusted. That is, the amount of the first negative electrode active material contained in the first negative electrode active material layer can be adjusted to optimize the capacity characteristics, and at the same time, the amount of the second negative electrode active material contained in the second negative electrode active material layer can be adjusted together so as not to reduce the capacity characteristics, and the surface reaction of the negative electrode can be suppressed to have the characteristic of enhancing the life characteristics.

[0050] In one embodiment of the present application, the first negative electrode active material contains at least one selected from the group consisting of SiOx (x = 0) and SiOx (0 < x < 2), and may contain 95 parts by weight or more of the SiOx (x = 0) based on 100 parts by weight of the first negative electrode active material.

[0051] In one embodiment of the present application, the first negative electrode active material contains at least one selected from the group consisting of SiOx (x = 0) and SiOx (0 < x < 2), and based on 100 parts by weight of the first negative electrode active material, it contains 95 parts by weight or more of the SiOx (x = 0), preferably 97 parts by weight or more of the SiOx (x = 0), more preferably 99 parts by weight or more, and may contain 100 parts by weight or less.

[0052] In one embodiment of the present application, the first negative electrode active material may particularly use pure silicon (Si) particles. Using pure silicon (Si) as the first negative electrode active material means that, as described above, when the total amount of the first negative electrode active material is 100 parts by weight, it contains pure Si particles (SiOx (x = 0)) that are not combined with other particles or elements within the above range.

[0053] The first negative electrode active material used in the first negative electrode active material layer of the present invention undergoes a very complicated crystal change in the reaction of electrochemically absorbing, storing, and releasing lithium atoms. As the reaction of electrochemically absorbing, storing, and releasing lithium atoms progresses, the composition and crystal structure of the silicon particles change to Si (crystal structure: Fd3m), LiSi (crystal structure: I41 / a), Li2Si (crystal structure: C2 / m), Li7Si2 (Pbam), Li 22 Si5(F23), etc. In addition, the volume of silicon particles expands by about four times due to changes in the complex crystal structure. Therefore, repeated charge-discharge cycles can destroy silicon particles and form bonds between lithium atoms and silicon particles, damaging the lithium atom insertion sites that the silicon particles initially had, resulting in a significant decrease in cycle life.

[0054] In one embodiment of the present application, the first negative electrode active material may be composed of SiOx (x=0).

[0055] The first negative electrode active material layer according to the present application contains a first negative electrode active material, specifically pure silicon particles containing 95 parts by weight or more of SiOx (x=0). When a high content of pure silicon particles is included, the capacity characteristics are excellent, but the resultant non-uniform surface reaction causes a decrease in lifespan. Therefore, the second negative electrode active material layer according to the present invention contains a specific weight loading amount to solve the above problem.

[0056] Meanwhile, the average particle size (D50) of the first negative electrode active material of the present invention may be 3 μm to 10 μm, specifically 4 μm to 8 μm, and more specifically 5 μm to 7 μm. When the average particle size is within the above range, the specific surface area of ​​the particles is within an appropriate range, and the viscosity of the negative electrode slurry is formed within an appropriate range. This allows smooth dispersion of the particles constituting the negative electrode slurry. In addition, when the size of the first negative electrode active material is equal to or greater than the above lower limit range, the contact area between the silicon particles and the conductive material is excellent due to the complex of the conductive material and the binder in the negative electrode slurry, and the conductive network is more likely to be maintained, thereby increasing the capacity retention rate. Meanwhile, when the average particle size satisfies the above range, silicon particles that are too large are excluded, and the surface of the negative electrode is formed smoothly, thereby preventing the current density non-uniformity phenomenon during charging and discharging.

[0057] In one embodiment of the present application, the first negative electrode active material generally has a characteristic BET surface area. The BET surface area of ​​the first negative electrode active material is preferably less than 0.01 m 2 / g~150.0m 2 / g, more preferably 0.1m 2 / g~100.0m 2 / g, particularly preferably 0.2m 2 / g~80.0m 2 / g, most preferably 0.2m 2 / g~18.0m 2 / g. The BET surface area is measured according to DIN 66131 (using nitrogen).

[0058] In one embodiment of the present application, the first negative active material can be, for example, in crystalline or amorphous form, and is preferably not porous.The silicon particles are preferably spherical or shard particles.Alternatively, the silicon particles can also have a fibrous structure or be in the form of a silicon-containing film or coating.

[0059] In one embodiment of the present application, the first negative electrode active material may have a non-spherical morphology, and the sphericity thereof is, for example, 0.9 or less, for example, 0.7 to 0.9, for example, 0.8 to 0.9, for example, 0.85 to 0.9.

[0060] In this application, the circularity is determined by the following formula A-1, where A is the area and P is the perimeter. [Formula A-1] 4πA / P 2

[0061] In one embodiment of the present application, there is provided a negative electrode for a lithium secondary battery, wherein the first negative electrode active material is 60 parts by weight or more based on 100 parts by weight of the first negative electrode active material layer composition.

[0062] In yet another embodiment, the first negative electrode active material may contain 60 parts by weight or more, preferably 65 parts by weight or more, more preferably 70 parts by weight or more, and 95 parts by weight or less, preferably 90 parts by weight or less, more preferably 80 parts by weight or less, based on 100 parts by weight of the first negative electrode active material layer composition.

[0063] The first negative electrode active material layer composition according to the present application uses a first negative electrode active material having an extremely high capacity within the above range, and when used together with a second negative electrode active material layer described below, the capacity performance of the entire negative electrode is not reduced, and the problems of surface degradation during charging and discharging, uniformity during pre-lithiation, and life characteristics are solved.

[0064] In the past, graphite-based compounds were generally used as the negative electrode active material, but in recent years, as the demand for high-capacity batteries has increased, attempts to mix silicon-based compounds to increase capacity have been increasing. However, silicon-based compounds have a limitation in that their volume expands rapidly during the charge / discharge process, damaging the conductive path formed in the negative electrode active material layer and reducing the performance of the battery.

[0065] Therefore, in one embodiment of the present application, the first negative electrode active material layer composition may further include at least one selected from the group consisting of a first negative electrode conductive material; and a first negative electrode binder.

[0066] In this case, the first negative electrode conductive material and the first negative electrode binder contained in the first negative electrode active material layer composition may be any material commonly used in the art without any limitations.

[0067] In one embodiment of the present application, the first negative electrode conductive material may be any material that can be commonly used in the art without limitation, and may specifically include at least one selected from the group consisting of dot-shaped conductive materials; planar conductive materials; and linear conductive materials.

[0068] In one embodiment of the present application, the dot-like conductive material refers to a dot-like or spherical conductive material that can be used to improve the conductivity of the negative electrode and has conductivity without inducing a chemical change. Specifically, the dot-like conductive material may be at least one selected from the group consisting of natural graphite, artificial graphite, carbon black, acetylene black, ketjen black, channel black, furnace black, lamp black, thermal black, conductive fiber, fluorocarbon, aluminum powder, nickel powder, zinc oxide, potassium titanate, titanium oxide, and polyphenylene derivatives, and may preferably include carbon black in that it realizes high conductivity and has excellent dispersibility.

[0069] In one embodiment of the present application, the dot-shaped conductive material has a BET specific surface area of ​​40 m 2 / g or more 70m 2 / g or less, preferably 45m 2 / g or more 65m 2 / g or less, more preferably 50m 2 / g or more 60m 2 / g or less.

[0070] In one embodiment of the present application, the particle diameter of the dotted conductive material may be 10 nm to 100 nm, preferably 20 nm to 90 nm, and more preferably 20 nm to 60 nm.

[0071] In one embodiment of the present application, the first negative electrode conductive material may include a sheet conductive material.

[0072] The planar conductive material can improve conductivity by increasing surface contact between silicon particles in the negative electrode, and at the same time, can suppress the disconnection of the conductive path due to volume expansion, and can be expressed as a plate-type conductive material or a bulk-type conductive material.

[0073] In one embodiment of the present application, the sheet conductive material may include at least one selected from the group consisting of platelet graphite, graphene, graphene oxide, and graphite flakes, and may be preferably platelet graphite.

[0074] In one embodiment of the present application, the average particle size (D50) of the sheet conductive material may be 2 μm to 7 μm, specifically 3 μm to 6 μm, and more specifically 4 μm to 5 μm. If the above range is satisfied, the sufficient particle size does not cause an excessive increase in viscosity of the negative electrode slurry, and dispersion is easy. Therefore, when dispersing using the same equipment and time, the dispersion effect is excellent.

[0075] In one embodiment of the present application, the sheet conductive material provides a negative electrode composition having a D10 of 0.5 μm or more and 1.5 μm or less, a D50 of 2.5 μm or more and 3.5 μm or less, and a D90 of 7.0 μm or more and 15.0 μm or less.

[0076] In one embodiment of the present application, the sheet conductive material may be a sheet conductive material having a high BET specific surface area; or a sheet conductive material having a low specific surface area.

[0077] In one embodiment of the present application, the planar conductive material may be a planar conductive material with a high specific surface area; or a planar conductive material with a low specific surface area, without any restrictions. However, the planar conductive material in the present application may be affected to some extent by the effects of dispersion in terms of electrode performance, and it may be particularly desirable to use a planar conductive material with a low specific surface area that does not cause dispersion problems.

[0078] In one embodiment of the present application, the sheet conductive material has a BET specific surface area of ​​5 m 2 / g or more.

[0079] In another embodiment, the sheet conductive material has a BET specific surface area of ​​5 m 2 / g or more 500m 2 / g or less, preferably 5m 2 / g or more 300m 2 / g or less, more preferably 5m 2 / g or more 250m 2 / g or less.

[0080] In another embodiment, the sheet conductive material is a sheet conductive material having a high specific surface area, and the BET specific surface area is 50 m 2 / g or more 500m 2 / g or less, preferably 80m 2 / g or more 300m 2 / g or less, more preferably 100m 2 / g or more 300m 2 / g or less.

[0081] In another embodiment, the sheet conductive material is a sheet conductive material having a low specific surface area and a BET specific surface area of ​​5 m 2 / g or more 40m 2 / g or less, preferably 5m 2 / g or more 30m 2 / g or less, more preferably 5m 2 / g or more 25m 2 / g or less.

[0082] Other conductive materials may include linear conductive materials such as carbon nanotubes. The carbon nanotubes may be bundled carbon nanotubes. The bundled carbon nanotubes may include a plurality of carbon nanotube units. Specifically, unless otherwise specified, the term "bundle type" refers to a secondary shape in which a plurality of carbon nanotube units are arranged in a substantially uniform orientation with their longitudinal axes or entangled in a bundle or rope shape. The carbon nanotube unit has a graphite sheet having a nano-sized cylindrical shape and an sp2 bond structure. In this case, the graphite sheet may exhibit conductive or semiconductive properties depending on the angle and structure of the graphite sheet. The bundled carbon nanotubes may be more uniformly dispersed during the manufacture of the negative electrode than entangled carbon nanotubes, and may smoothly form a conductive network in the negative electrode, thereby improving the conductivity of the negative electrode.

[0083] In one embodiment of the present application, the linear conductive material may be a single-walled carbon nanotube; alternatively, a multi-walled carbon nanotube may be used.

[0084] The single-walled carbon nanotube is a material in which carbon atoms arranged in a hexagonal shape form a tube, and depending on its unique chirality, it can exhibit non-conductive, fully conductive or semiconductive properties. The carbon atoms are linked by strong covalent bonds, and the material has tensile strength about 100 times greater than that of steel, excellent flexibility and elasticity, and is chemically stable.

[0085] The average diameter of the single-walled carbon nanotubes is 0.5 nm to 15 nm. According to an embodiment of the present invention, the average diameter of the single-walled carbon nanotubes may be 1 nm to 10 nm, or 1 nm to 5 nm, or 1 nm to 2 nm. When the average diameter of the single-walled carbon nanotubes satisfies such a range, the electrical conductivity of the negative electrode can be maintained even if the single-walled carbon nanotubes are contained in a very small content, and a preferable viscosity and solid content can be derived during the preparation of the conductive material dispersion. In the conductive material dispersion, the single-walled carbon nanotubes may be present in an entangled state (aggregate) in which they are entangled with each other. Therefore, the average diameter can be derived by confirming the diameter of any entangled single-walled carbon nanotube aggregate extracted from the conductive material dispersion by SEM or TEM, and then dividing the diameter of the aggregate by the number of single-walled carbon nanotubes constituting the aggregate.

[0086] The BET specific surface area of ​​the single-walled carbon nanotubes is 500 m 2 / g~1,500m 2 / g, or 900m 2 / g~1,200m 2 / g, specifically 250m 2 / g~330m 2 / g. When the above range is satisfied, a conductive material dispersion having a desired solid content is obtained, and the viscosity of the negative electrode slurry is prevented from excessively increasing. The BET specific surface area can be measured by a nitrogen adsorption BET method.

[0087] The aspect ratio of the single-walled carbon nanotube may be 50 to 20,000, or the length of the single-walled carbon nanotube may be 5 to 100 μm, or 5 to 50 μm. When the aspect ratio or length is within this range, the specific surface area is high, so that the single-walled carbon nanotube can be strongly attracted to the active material particles in the negative electrode. As a result, the conductive network can be smoothly maintained even when the negative electrode active material expands in volume. The aspect ratio can be determined by averaging the aspect ratios of 15 single-walled carbon nanotubes with a large aspect ratio and 15 single-walled carbon nanotubes with a small aspect ratio when observing the single-walled carbon nanotube powder through a SEM.

[0088] The single-walled carbon nanotube has a larger aspect ratio, a longer length, and a larger volume than multi-walled or double-walled carbon nanotubes, and is therefore advantageous in that an electrical network can be constructed even when only a small amount is used.

[0089] In one embodiment of the present application, the first negative electrode conductive material may be 10 parts by weight or more and 40 parts by weight or less based on 100 parts by weight of the first negative electrode active material layer composition.

[0090] In yet another embodiment, the first negative electrode conductive material may include 10 parts by weight or more and 40 parts by weight or less, preferably 10 parts by weight or more and 30 parts by weight or less, and more preferably 15 parts by weight or more and 25 parts by weight or less, based on 100 parts by weight of the first negative electrode active material layer composition.

[0091] In one embodiment of the present application, the first negative electrode conductive material includes dot-like conductive material; sheet-like conductive material; and linear conductive material, and the dot-like conductive material:sheet-like conductive material:linear conductive material may satisfy a ratio of 1:1:0.01 to 1:1:1.

[0092] In one embodiment of the present application, the dot-shaped conductive material may be in the range of 1 part by weight or more and 60 parts by weight or less, preferably 5 parts by weight or more and 50 parts by weight or less, and more preferably 10 parts by weight or more and 50 parts by weight or less, based on 100 parts by weight of the first negative electrode conductive material.

[0093] In one embodiment of the present application, the sheet conductive material may satisfy the range of 1 part by weight or more and 60 parts by weight or less, preferably 5 parts by weight or more and 50 parts by weight or less, and more preferably 10 parts by weight or more and 50 parts by weight or less, based on 100 parts by weight of the first negative electrode conductive material.

[0094] In one embodiment of the present application, the linear conductive material may satisfy the range of 0.01 parts by weight or more and 10 parts by weight or less, preferably 0.05 parts by weight or more and 8 parts by weight or less, and more preferably 0.1 parts by weight or more and 5 parts by weight or less, based on 100 parts by weight of the first negative electrode conductive material.

[0095] In one embodiment of the present application, the first negative electrode conductive material may include a linear conductive material; and a planar conductive material.

[0096] In one embodiment of the present application, the first negative electrode conductive material may include a linear conductive material and a sheet conductive material, and a ratio of the linear conductive material:sheet conductive material may satisfy 0.01:1 to 0.1:1.

[0097] In one embodiment of the present application, there is provided a negative electrode composition, in which the first negative electrode conductive material includes a dot-like conductive material and a sheet-like conductive material, and the negative electrode composition includes, based on 100 parts by weight of the first negative electrode conductive material, 45 to 60 parts by weight of the dot-like conductive material; and 40 to 55 parts by weight of the sheet-like conductive material.

[0098] In still another embodiment, the first negative electrode conductive material includes a dot-like conductive material and a sheet-like conductive material, and may contain 45 to 60 parts by weight, preferably 47 to 58 parts by weight, and more preferably 50 to 55 parts by weight of the dot-like conductive material based on 100 parts by weight of the first negative electrode conductive material.

[0099] In yet another embodiment, the first negative electrode conductive material includes dot-shaped conductive material and sheet-shaped conductive material, and may contain 40 to 55 parts by weight, preferably 42 to 53 parts by weight, and more preferably 45 to 50 parts by weight of the sheet-shaped conductive material based on 100 parts by weight of the first negative electrode conductive material.

[0100] In one embodiment of the present application, the ratio of the dot-like conductive material:sheet-like conductive material may satisfy 1:1.

[0101] In one embodiment of the present application, the first negative electrode conductive material satisfies the above composition and ratio, so that the battery does not have a significant effect on the life characteristics of existing lithium secondary batteries, and the number of points at which charging and discharging can be performed increases, resulting in excellent output characteristics at a high C-rate.

[0102] The first negative electrode conductive material according to the present application has a completely different structure from the conductive material applied to the positive electrode. That is, the first negative electrode conductive material according to the present application serves to form a contact between silicon-based active materials whose volumetric expansion in the electrode is extremely large due to charging and discharging, while the positive electrode conductive material serves to provide some conductivity while acting as a buffer when rolled, and has a completely different structure and role from the negative electrode conductive material of the present invention.

[0103] In addition, the first negative electrode conductive material according to the present application is applied to a silicon-based active material, and has a completely different structure from a conductive material applied to a graphite-based active material. That is, a conductive material used in an electrode having a graphite-based active material has particles that are simply smaller than the active material, and therefore has the properties of improving output characteristics and imparting some electrical conductivity, and has a completely different structure and role from the first negative electrode conductive material applied together with a silicon-based active material as in the present invention.

[0104] In one embodiment of the present application, the first negative electrode binder may include at least one selected from the group consisting of polyvinylidene fluoride-hexafluoropropylene copolymer (PVDF-co-HFP), polyvinylidene fluoride, polyacrylonitrile, polymethylmethacrylate, polyvinyl alcohol, carboxymethyl cellulose (CMC), starch, hydroxypropyl cellulose, regenerated cellulose, polyvinylpyrrolidone, tetrafluoroethylene, polyethylene, polypropylene, polyacrylic acid, ethylene-propylene-diene monomer (EPDM), sulfonated EPDM, styrene butadiene rubber (SBR), fluororubber, polyacrylic acid, and substances in which hydrogen of these substances is substituted with Li, Na, Ca, or the like, and may also include various copolymers thereof.

[0105] The first negative electrode binder according to one embodiment of the present application serves to capture the first negative electrode active material and the first negative electrode conductive material in order to prevent twisting and structural deformation of the negative electrode structure during volume expansion and relaxation of the first negative electrode active material. Any of the general binders that fulfill the above-mentioned role may be applied, specifically, a water-based binder may be used, and more specifically, a PAM-based binder may be used.

[0106] In one embodiment of the present application, the first negative electrode binder may include 30 parts by weight or less, preferably 25 parts by weight or less, more preferably 20 parts by weight or less, and may include 5 parts by weight or more, or 10 parts by weight or more, based on 100 parts by weight of the first negative electrode active material layer composition.

[0107] In comparison with the conventional carbon-based negative electrode, when a silicon-based negative electrode is used, a water-based binder is applied in the above weight parts, and a dot-shaped conductive material can be used. Due to the above characteristics, the dot-shaped conductive material has hydrophobicity and excellent bonding strength between the conductive material and the binder.

[0108] In one embodiment of the present application, the second negative electrode active material includes one or more mixtures selected from the group consisting of a carbon-based active material, a silicon-based active material, a metal-based active material capable of alloying with lithium, and a lithium-containing nitride, and the silicon-based active material may be 1 part by weight or more and 100 parts by weight or less based on 100 parts by weight of the second negative electrode active material.

[0109] In another embodiment, the second negative electrode active material includes one or more and three or less mixtures selected from the group consisting of a carbon-based active material, a silicon-based active material, a metal-based active material capable of alloying with lithium, and a lithium-containing nitride, and the silicon-based active material may be 1 part by weight or more and 100 parts by weight or less based on 100 parts by weight of the second negative electrode active material.

[0110] In another embodiment, the second negative electrode active material may include a carbon-based active material and a silicon-based active material.

[0111] In one embodiment of the present application, there is provided a negative electrode for a lithium secondary battery, wherein the second negative electrode active material includes a silicon-based active material and a carbon-based active material, and includes 1 part by weight or more and 95 parts by weight or less of the silicon-based active material based on 100 parts by weight of the second negative electrode active material.

[0112] In one embodiment of the present application, the silicon-based active material included in the second negative electrode active material may include one or more selected from the group consisting of SiOx (0 < x < 2), SiC, and Si alloys.

[0113] In one embodiment of the present application, the silicon-based active material included in the second negative electrode active material includes at least one selected from the group consisting of SiOx (0 < x < 2), SiC, and Si alloys, and may include 1 part by weight or more of SiOx (0 < x < 2) based on 100 parts by weight of the second negative electrode active material.

[0114] In another embodiment, the silicon-based active material contained in the second negative electrode active material includes at least one selected from the group consisting of SiOx (0 < x < 2), SiC, and Si alloy. Based on 100 parts by weight of the second negative electrode active material, SiOx (0 < x < 2) can be included in an amount of 1 part by weight or more and 10 parts by weight or more, and may be included in an amount of 99 parts by weight or less.

[0115] In another embodiment, the silicon-based active material contained in the second negative electrode active material may include SiOx (0 < x < 2).

[0116] In another embodiment, the silicon-based active material contained in the second negative electrode active material may include SiC.

[0117] The negative electrode for a lithium secondary battery according to the present application includes the second negative electrode active material in the second negative electrode active material layer as described above. Thereby, while maintaining the characteristics of high capacity and high density including the above-described first negative electrode active material, the second negative electrode active material serves as a buffer layer, and thus has the characteristics of being able to solve the surface degradation problem during charge and discharge, the uniformity problem during prelithiation, and the life characteristic problem.

[0118] In one embodiment of the present application, typical examples of the carbon-based active material include natural graphite, artificial graphite, expanded graphite, carbon fiber, graphitizable carbon, carbon black, carbon nanotube, fullerene, or activated carbon, etc. As long as it is commonly used for carbon materials for lithium secondary batteries, it can be used without limitation, and specifically, it may be processed into a spherical or dot-like form for use.

[0119] Provided is a negative electrode for a lithium secondary battery, in which the carbon-based active material includes graphite in one embodiment of the present application, the graphite includes artificial graphite and natural graphite, and the weight ratio of the artificial graphite to the natural graphite is 5:5 to 9.5:0.5.

[0120] The artificial graphite according to an embodiment of the present invention may be in the form of primary particles, or may be in the form of secondary particles in which a plurality of the primary particles are aggregated.

[0121] The term "primary particle" as used in the present invention means the original particle from which other types of particles are formed, and multiple primary particles can aggregate, combine or granulate to form secondary particles.

[0122] As used herein, the term "secondary particles" refers to larger, physically distinct particles formed by the aggregation, bonding, or granulation of individual primary particles.

[0123] The primary particle artificial graphite may be produced by heat treating one or more selected from the group consisting of needle cokes, mosaic cokes, and coal tar pitch.

[0124] The artificial graphite is generally produced by carbonizing raw materials such as coal tar, coal tar pitch, and heavy petroleum oil at 2,500°C or higher, and can be used as an anode active material after such graphitization and adjusting the particle size by crushing and forming secondary particles. In the case of artificial graphite, crystals are randomly distributed within the particles, and compared to natural graphite, it has a lower degree of spheroidization and a slightly pointed shape.

[0125] The artificial graphite used in an embodiment of the present invention may be commercially available mesophase carbon microbeads (MCMB), mesophase pitch-based carbon fiber (MPCF), artificial graphite graphitized in a block form, artificial graphite graphitized in a powder form, etc. The sphericity of the artificial graphite may be 0.91 or less, or 0.6 to 0.91, or 0.7 to 0.9.

[0126] The artificial graphite may have a particle size of 5 μm to 30 μm, preferably 10 μm to 25 μm.

[0127] Specifically, the D50 of the primary particles of the artificial graphite may be 6 μm to 15 μm, 6 μm to 10 μm, or 6 μm to 9 μm. When the D50 of the primary particles satisfies this range, the primary particles can be formed to a degree that has high graphitization, and the orientation index of the negative electrode active material particles can be appropriately ensured, thereby improving the rapid filling performance.

[0128] The secondary particles of the artificial graphite may be formed by granulating primary particles. That is, the secondary particles may be structures formed by agglomerating the primary particles to each other through a granulation process. The secondary particles may include a carbonaceous matrix that aggregates the primary particles. The carbonaceous matrix may include at least one of soft carbon and graphite. The soft carbon may be formed by heat treating pitch.

[0129] The carbonaceous matrix may be contained in the secondary particles in an amount of 8% by weight to 16% by weight, specifically 9% by weight to 12% by weight. This range is a lower level than the carbonaceous matrix content used in ordinary secondary particles of artificial graphite. This is because the particle size of the primary particles in the secondary particles is controlled, and structurally stable secondary particles can be produced even if the content of the carbonaceous matrix required for granulation is small, and the amount of primary particles constituting the secondary particles can be uniform.

[0130] The secondary particles of the artificial graphite may include a carbon coating layer on a surface thereof, the carbon coating layer including at least one of amorphous carbon and crystalline carbon.

[0131] The crystalline carbon may further improve the electrical conductivity of the negative electrode active material. The crystalline carbon may include at least one selected from the group consisting of fullerene and graphene.

[0132] The amorphous carbon can appropriately maintain the strength of the coating layer and suppress the expansion of the natural graphite. The amorphous carbon may be a carbon-based material formed by using at least one carbide selected from the group consisting of tar, pitch, and other organic substances, or a hydrocarbon as a source in a chemical vapor deposition process.

[0133] The other carbonized organic matter may be a carbonized organic matter selected from carbonized sucrose, glucose, galactose, fructose, lactose, mannose, ribose, aldohexose or ketohexose, and combinations thereof.

[0134] The D50 of the secondary particles of the artificial graphite may be 10 μm to 25 μm, specifically 12 μm to 22 μm, and more specifically 13 μm to 20 μm. When the artificial graphite secondary particles satisfy the above range, the artificial graphite secondary particles can be uniformly dispersed in the slurry, and the charging performance of the battery can be improved.

[0135] The tap density of the secondary particles of artificial graphite may be 0.85 g / cc to 1.30 g / cc, specifically 0.90 g / cc to 1.10 g / cc, and more specifically 0.90 g / cc to 1.07 g / cc. When the tap density satisfies the above range, the secondary particles of artificial graphite can be smoothly packed in the negative electrode, which means that the adhesive strength of the negative electrode can be improved.

[0136] The natural graphite may generally consist of plate-like agglomerates before being processed, and the plate-like particles may be processed into spherical shapes having smooth surfaces by post-processing such as particle crushing and reassembly processes in order to be used as an active material for electrode manufacture.

[0137] The natural graphite used in one embodiment of the present invention may have a sphericity of more than 0.91 and less than or equal to 0.97, or from 0.93 to 0.97, or from 0.94 to 0.96.

[0138] The natural graphite may have a particle size of 5 μm to 30 μm, or 10 μm to 25 μm.

[0139] According to an embodiment of the present invention, the weight ratio of the artificial graphite to the natural graphite may be 5:5 to 9.5:0.5, or 5:5 to 9.3:0.7, or 5:5 to 9:1, or 6:4 to 9:1. When the weight ratio of the artificial graphite to the natural graphite satisfies such a range, a better output may be exhibited, which may be advantageous in terms of life span and quick charging performance.

[0140] In one embodiment of the present application, the planar conductive material used as the negative electrode conductive material has a structure and role different from that of the carbon-based active material generally used as the negative electrode active material. Specifically, the carbon-based active material used as the negative electrode active material may be artificial graphite or natural graphite, and refers to a material that is processed into a spherical or dot-like shape to facilitate the storage and release of lithium ions.

[0141] Meanwhile, the planar conductive material used as the negative electrode conductive material is a material having a planar or plate-like shape and can be expressed as plate-shaped graphite. That is, it is a material contained in the negative electrode active material layer to maintain a conductive path, and does not play a role in storing and releasing lithium, but rather means a material to ensure a planar conductive path inside the negative electrode active material layer.

[0142] That is, in the present application, the use of plate-shaped graphite as a conductive material means that it is processed into a planar or plate-shaped form and is used as a material that ensures a conductive path, rather than storing or releasing lithium. In this case, the negative electrode active material contained therein has high capacity characteristics for storing and releasing lithium, and plays a role in storing and releasing all the lithium ions transferred from the positive electrode.

[0143] Meanwhile, in the present application, the use of a carbon-based active material as an active material means that the carbon-based active material is processed into a dot-like or spherical shape and is used as a material that stores or releases lithium.

[0144] That is, in one embodiment of the present application, the carbon-based active material, artificial graphite or natural graphite, has a BET specific surface area of ​​0.1 m 2 / g or more 4.5m 2 / g or less. The plate-shaped graphite, which is a planar conductive material, may be planar and have a BET specific surface area of ​​5 m 2 / g or more.

[0145] Representative examples of the metal-based active material include compounds containing one or more metal elements selected from the group consisting of Al, Sn, Ag, Bi, Mg, Zn, In, Ge, Pb, Pd, Pt, Ti, Sb, Ga, Mn, Fe, Co, Ni, Cu, Sr, and Ba. These metal compounds may be used in any form, such as a simple substance, an alloy, an oxide (TiO2, SnO2, etc.), a nitride, a sulfide, a boride, or an alloy with lithium, but the simple substance, the alloy, the oxide, and the alloy with lithium can be made to have a high capacity.

[0146] In one embodiment of the present application, there is provided a negative electrode for a lithium secondary battery, in which the second negative electrode active material is contained in an amount of 60 parts by weight or more based on 100 parts by weight of a second negative electrode active material layer composition.

[0147] In still another embodiment, the second negative electrode active material may be 60 parts by weight or more, 100 parts by weight or less, or 99 parts by weight or less, based on 100 parts by weight of the second negative electrode active material layer composition.

[0148] The second negative electrode active material layer composition according to the present application has lower capacity characteristics than the first negative electrode active material, but by using the second negative electrode active material in the above range, which has less particle cracking due to charging and discharging, it is possible to have the characteristics of improving the life characteristics by suppressing the surface reaction of the negative electrode without reducing the capacity performance of the negative electrode.

[0149] In one embodiment of the present application, there is provided a negative electrode for a lithium secondary battery, wherein the second negative electrode active material layer composition further comprises at least one selected from the group consisting of a second negative electrode conductive material; and a second negative electrode binder.

[0150] In this case, the second negative electrode conductive material and the second negative electrode binder may be similar to the first negative electrode conductive material and the first negative electrode binder described above.

[0151] In one embodiment of the present application, the second negative electrode active material layer provides a negative electrode for a lithium secondary battery that satisfies the following formula 1. [Formula 1] 0.5≦B / A≦2 In the above formula 1, A is the discharge capacity of the second negative electrode active material layer, B refers to the capacity of pre-lithiation lithium.

[0152] In one embodiment of the present application, the formula 1 may satisfy the range of 0.5≦B / A≦2, preferably 0.7≦B / A≦1.8, and more preferably 0.9≦B / A≦1.6. The upper and lower limit values ​​may be applied in combination. Specifically, various combinations of values ​​from 0.5, 0.6, 0.7, 0.8, 0.9, 1.0, 1.1, 1.2, 1.3, 1.4, 1.5, 1.6, 1.7, 1.8, 1.9, and 2.0 may be used. As an example, 0.6≦B / A≦1.9, 0.8≦B / A≦1.7, 1.0≦B / A≦1.5, 1.1≦B / A≦1.4, and 1.2≦B / A≦1.3 may be used.

[0153] The negative electrode for a lithium secondary battery according to the present application has two negative electrode active material layers. In particular, the negative electrode according to the present application undergoes a pre-lithiation process to limit the usage ratio of silicon-based active material during initial charging and discharging, prevent degradation of the electrode surface, and further provide a role as a reservoir. At this time, the pre-lithiation ratio of the above formula 1 is satisfied based on the discharge capacity of silicon contained in the second negative electrode active material layer composition, and the capacity characteristics and life characteristics are optimized to provide excellent effects.

[0154] The maximum charge depth for realizing the life performance of Si is usually at the level of 100 mV, and below this range, a crystalline phase of LixSiy is formed. At this time, when the range of x / y value is 3.75 or more, a crystalline phase is generated. Therefore, when the range of the formula 1 is exceeded, Li is deeply filled up to the first negative electrode active material of the first negative electrode active material layer and cycles proceed, the volume of Si particles increases, the effect of pulverization becomes more severe, and fading occurs quickly. In addition, when the range of the formula 1 is exceeded, it is difficult to expect an increase in life characteristics, which is an effect of pre-lithiation.

[0155] As a result, the negative electrode for a lithium secondary battery according to the present application has a double layer structure in which a second negative electrode active material layer is coated as a buffer layer for a first negative electrode active material layer, and is characterized in that, in particular, during pre-lithiation, the first negative electrode active material layer is minimized from being pre-lithiated while maximizing life characteristics by satisfying the range of Formula 1.

[0156] In one embodiment of the present application, the negative electrode for the lithium secondary battery may be pre-lithiated.

[0157] The negative electrode for a lithium secondary battery according to the present application is composed of a double layer, and in particular, the second negative electrode active material layer having a specific loading amount serves as a buffer layer during pre-lithiation and also serves to assist in uniform lithiation in the depth direction of the electrode during cycle charging and discharging.

[0158] In one embodiment of the present application, a step of preparing a negative electrode current collector layer; a step of applying a first negative electrode active material layer composition to one or both surfaces of the negative electrode current collector layer to form a first negative electrode active material layer; and a step of applying a second negative electrode active material layer composition to the opposite surface of the first negative electrode active material layer in contact with the negative electrode current collector layer to form a second negative electrode active material layer; A method for manufacturing a negative electrode for a lithium secondary battery, wherein the first negative electrode active material includes at least one selected from the group consisting of SiOx (x = 0) and SiOx (0 < x < 2), and based on 100 parts by weight of the first negative electrode active material, 95 parts by weight or more of SiOx (x = 0) is included, and the second negative electrode active material includes one or more mixtures selected from the group consisting of a carbon-based active material, a silicon-based active material, a metal-based active material capable of alloying with lithium, and a lithium-containing nitride. The silicon-based active material is 1 part by weight or more and 99 parts by weight or less based on 100 parts by weight of the second negative electrode active material, and the second negative electrode active material layer satisfies the following formula 1. Provided is a method for manufacturing a negative electrode for a lithium secondary battery.

[0159] In the method for manufacturing the negative electrode, the composition and content included in each step can be applied to the foregoing content.

[0160] In one embodiment of the present application, a step of applying a first negative electrode active material layer composition to one or both surfaces of the negative electrode current collector layer to form a first negative electrode active material layer is provided.

[0161] That is, the step is a step of forming an active material layer on the negative electrode current collector layer, and in the double layer structure, it can mean a step of forming an active material layer on the surface (lower layer part) in contact with the negative electrode current collector layer.

[0162] In one embodiment of the present application, applying the first negative electrode active material layer composition includes applying and drying a first negative electrode slurry including the first negative electrode active material layer composition and a negative electrode slurry solvent.

[0163] At this time, the solid content of the first negative electrode slurry can satisfy the range of 10% to 40%.

[0164] In one embodiment of the present application, forming the first negative electrode active material layer may include mixing the first negative electrode slurry, and coating the mixed first negative electrode slurry on one or both sides of the negative electrode current collector layer, and the coating may be performed using a coating method commonly used in the art.

[0165] In addition, the weight loading amount of the first negative electrode active material layer composition may be used interchangeably with the weight loading amount of the first negative electrode slurry.

[0166] In one embodiment of the present application, a step of forming a second negative electrode active material by coating a second negative electrode active material layer composition on a surface of the first negative electrode active material layer opposite to a surface in contact with the negative electrode current collector layer is provided.

[0167] That is, the step is a step of forming a second negative electrode active material layer on the first negative electrode active material layer, and may refer to a step of forming an active material layer on a surface (upper layer) away from the negative electrode current collector layer in a double layer structure.

[0168] In one embodiment of the present application, applying the second negative electrode active material layer composition includes applying and drying a second negative electrode slurry including the second negative electrode active material layer composition; and a negative electrode slurry solvent.

[0169] At this time, the solid content of the second negative electrode slurry may be in the range of 10% to 40%.

[0170] In one embodiment of the present application, there is provided a method for manufacturing a negative electrode for a lithium secondary battery, wherein the step of forming the second negative electrode active material layer includes the steps of: mixing the second negative electrode slurry; and coating the mixed second negative electrode slurry on a surface of the first negative electrode active material layer opposite to a surface in contact with the negative electrode current collector layer.

[0171] The coating may be performed using a coating method commonly used in the art.

[0172] In addition, the weight loading amount of the second negative electrode active material layer composition may be used interchangeably with the weight loading amount of the second negative electrode slurry.

[0173] The description of the forming of the first negative electrode active material layer may be similarly applied to the forming of the second negative electrode active material layer.

[0174] In one embodiment of the present application, there is provided a method for manufacturing a negative electrode for a lithium secondary battery, wherein the step of forming the second negative electrode active material layer on the first negative electrode active material layer includes a wet on dry process or a wet on wet process.

[0175] In one embodiment of the present application, the wet-on-dry process may refer to a process of applying a first negative electrode active material layer composition, partially or completely drying it, and applying a second negative electrode active material layer composition thereon.

[0176] 5 is a flow chart showing a wet on dry process according to an embodiment of the present application. Specifically, in the wet on dry process, a first negative electrode slurry mixture (first negative electrode active material, first negative electrode conductive agent, first negative electrode binder, first solvent) is prepared and applied to a negative electrode current collector layer. The first negative electrode slurry mixture is then dried to form a first negative electrode active material layer. A second negative electrode slurry mixture is then prepared and applied to the first negative electrode active material layer, and dried to form a second negative electrode active material layer. Each layer is then rolled and compressed to form a negative electrode for a lithium secondary battery according to the present application.

[0177] In one embodiment of the present application, the wet-on-wet process refers to a process in which a first negative electrode active material layer composition is applied, and then a second negative electrode active material layer composition is applied thereon without drying.

[0178] 6 is a flow chart showing a wet on wet process according to one embodiment of the present application. Specifically, in the wet on wet process, a first negative electrode slurry mixture is prepared and applied to a negative electrode current collector layer, and at the same time, a second negative electrode slurry mixture is prepared and applied to the first negative electrode slurry mixture, and the first and second negative electrode slurry mixtures are dried. Then, each layer is rolled and pressed to form a negative electrode for a lithium secondary battery according to the present application.

[0179] In one embodiment of the present application, there is provided a method for manufacturing a negative electrode for a lithium secondary battery, wherein the step of forming the second negative electrode active material layer on the first negative electrode active material layer includes a wet on dry process, the wet on dry process including the steps of: applying a first negative electrode active material layer composition; partially or fully drying the applied first negative electrode active material layer composition to form a first negative electrode active material layer; and applying the second negative electrode active material layer composition on the first negative electrode active material layer.

[0180] In one embodiment of the present application, there is provided a method for manufacturing a negative electrode for a lithium secondary battery, wherein the step of forming the second negative electrode active material layer on the first negative electrode active material layer includes a wet-on-wet process, the wet-on-wet process including: applying a first negative electrode active material layer composition; and applying the second negative electrode active material layer composition to the first negative electrode active material layer composition while the first negative electrode active material layer composition is in a wet state.

[0181] In particular, the wet on dry process involves coating a first negative electrode active material layer composition, partially or completely drying it, and then coating a second negative electrode active material layer composition on top of it, and through the above process, the first negative electrode active material layer and the second negative electrode active material layer can have a clear boundary, which allows the compositions contained in the first negative electrode active material layer and the second negative electrode active material layer to be formed into a double layer without being mixed.

[0182] In one embodiment of the present application, the negative electrode slurry solvent may be used without limitation as long as it can dissolve the first negative electrode active material layer composition and the second negative electrode active material layer composition, and specifically, water or NMP may be used.

[0183] As a result of the wet-on-wet process, a junction region where the first and second negative electrode active material layers are mixed may be formed. In order for the wet-on-wet process to occur, the viscosity of the first negative electrode active material layer composition must be lower than the viscosity of the second negative electrode active material layer composition, so that intermixing may occur in the junction region and process.

[0184] In addition, the second negative electrode active material layer is formed after the first negative electrode active material layer is dried (wet on dry process), so that the interface between the two layers is clearly separated.

[0185] On the other hand, if the second negative electrode active material layer is applied before the first negative electrode active material layer composition is completely dry (the first negative electrode active material layer composition and the second negative electrode active material layer composition are applied simultaneously), mixing occurs at the interface between the two layers, and a bonding region is formed.

[0186] In one embodiment of the present application, there is provided a method for producing a negative electrode for a lithium secondary battery, the method including a step of pre-lithiating a negative electrode in which a first negative electrode active material layer and a second negative electrode active material layer are formed on the negative electrode current collector layer, the step of pre-lithiating the negative electrode including a lithium electrolytic plating process; a lithium metal transfer process; a lithium metal deposition process; or a stabilized lithium metal powder (SLMP) coating process.

[0187] As described above, the second negative electrode active material layer contains the above-mentioned second negative electrode active material, and is provided with a mixed composition of a silicon-based active material and a carbon-based active material, which allows the advantage of rapid filling to be retained, and in particular, since the second negative electrode active material has a mixed composition and is highly irreversible, it can be advantageously effective in the pre-lithiation process in which the negative electrode is pre-charged. Compared to the case where only the first negative electrode active material layer is applied, the second negative electrode active material has the second negative electrode active material having the above-mentioned composition, and a uniform pre-lithiation process can be performed on the upper end of the negative electrode, which provides an improved lifespan.

[0188] In one embodiment of the present application, the porosity of the first and second negative electrode active material layers may be in the range of 10% or more and 60% or less.

[0189] In still another embodiment, the porosity of the first and second negative electrode active material layers may be in the range of 10% or more and 60% or less, preferably 20% or more and 50% or less, and more preferably 30% or more and 45% or less.

[0190] The porosity varies depending on the composition and content of the active material, conductive material, and binder contained in the first and second negative electrode active material layers, and is characterized by the fact that the electrode has an appropriate range of electrical conductivity and resistance.

[0191] In one embodiment of the present application, there is provided a lithium secondary battery comprising: a positive electrode; a negative electrode for a lithium secondary battery according to the present application; a separator provided between the positive electrode and the negative electrode; and an electrolyte.

[0192] A secondary battery according to an embodiment of the present specification may include, in particular, the negative electrode for a lithium secondary battery described above. Specifically, the secondary battery may include a negative electrode, a positive electrode, a separator and an electrolyte interposed between the positive electrode and the negative electrode, and the negative electrode is the same as the negative electrode described above. The negative electrode has been described above, so a detailed description thereof will be omitted.

[0193] The positive electrode may include a positive electrode current collector layer and a positive electrode active material layer formed on the positive electrode current collector layer and including a positive electrode active material.

[0194] In the positive electrode, the positive electrode current collector layer is not particularly limited as long as it does not induce chemical changes in the battery and has conductivity, and for example, stainless steel, aluminum, nickel, titanium, baked carbon, or aluminum or stainless steel surface-treated with carbon, nickel, titanium, silver, etc. may be used. In addition, the positive electrode current collector layer may usually have a thickness of 3 μm to 500 μm, and fine irregularities may be formed on the surface of the current collector to increase the adhesive strength of the positive electrode active material. For example, it may be used in various forms such as a film, sheet, foil, net, porous body, foam, nonwoven fabric, etc.

[0195] The positive electrode active material may be a commonly used positive electrode active material. Specifically, the positive electrode active material may be a layered compound such as lithium cobalt oxide (LiCoO2), lithium nickel oxide (LiNiO2), or a compound substituted with one or more transition metals; a lithium iron oxide such as LiFe3O4; 1+c1 Mn 2-c1 O4 (0≦c1≦0.33), lithium manganese oxides such as LiMnO3, LiMn2O3, LiMnO2; lithium copper oxide (Li2CuO2); vanadium oxides such as LiV3O8, V2O5, Cu2V2O7; chemical formula LiNi 1-c2 M c2 Lithium nickel oxide with Ni site represented by the chemical formula LiMnO2 (wherein M is at least one selected from the group consisting of Co, Mn, Al, Cu, Fe, Mg, B and Ga, and satisfies 0.01≦c2≦0.3); 2-c3 M c3Examples of the lithium manganese composite oxide include, but are not limited to, lithium manganese composite oxide represented by Li2Mn3MO8 (wherein M is at least one selected from the group consisting of Co, Ni, Fe, Cr, Zn, and Ta, and satisfies 0.01≦c3≦0.1) or Li2Mn3MO8 (wherein M is at least one selected from the group consisting of Fe, Co, Ni, Cu, and Zn); and LiMn2O4 in which part of the Li in the chemical formula is replaced with an alkaline earth metal ion. The positive electrode may be Li-metal.

[0196] The positive electrode active material layer may contain a positive electrode conductive material and a positive electrode binder in addition to the above-mentioned positive electrode active material.

[0197] In this case, the positive electrode conductive material is used to give conductivity to the electrode, and can be used without any particular limitation as long as it does not cause chemical changes in the battery that is constructed and has electronic conductivity.Specific examples include graphite such as natural graphite and artificial graphite; carbon-based materials such as carbon black, acetylene black, ketjen black, channel black, furnace black, lamp black, thermal black, and carbon fiber; metal powder or metal fiber such as copper, nickel, aluminum, and silver; conductive whiskers such as zinc oxide and potassium titanate; conductive metal oxides such as titanium oxide; or conductive polymers such as polyphenylene derivatives, and the like, and one or a mixture of two or more of these may be used alone.

[0198] The positive electrode binder plays a role of improving the adhesion between the positive electrode active material particles and the adhesive strength between the positive electrode active material and the positive electrode current collector. Specific examples include polyvinylidene fluoride (PVDF), vinylidene fluoride-hexafluoropropylene copolymer (PVDF-co-HFP), polyvinyl alcohol, polyacrylonitrile, carboxymethyl cellulose (CMC), starch, hydroxypropyl cellulose, regenerated cellulose, polyvinylpyrrolidone, tetrafluoroethylene, polyethylene, polypropylene, ethylene-propylene-diene polymer (EPDM), sulfonated-EPDM, styrene-butadiene rubber (SBR), fluororubber, or various copolymers thereof, and one or more of these may be used alone or in combination.

[0199] The separator is a membrane that separates the negative electrode and the positive electrode to provide a passage for lithium ions to move. Any separator that is generally used in secondary batteries can be used without any particular restrictions. In particular, a separator that has low resistance to the movement of electrolyte ions and has excellent electrolyte humidification ability is preferred. Specifically, a porous polymer film, for example, a porous polymer film made of a polyolefin polymer such as an ethylene homopolymer, a propylene homopolymer, an ethylene / butene copolymer, an ethylene / hexene copolymer, and an ethylene / methacrylate copolymer, or a laminate structure of two or more layers thereof may be used. In addition, a conventional porous nonwoven fabric, for example, a nonwoven fabric made of high-melting glass fiber, polyethylene terephthalate fiber, etc. may be used. In addition, in order to ensure heat resistance or mechanical strength, a coated separator containing a ceramic component or a polymeric substance may be used, and may be selectively used in a single layer or multilayer structure.

[0200] Examples of the electrolyte include organic liquid electrolytes, inorganic liquid electrolytes, solid polymer electrolytes, gel-type polymer electrolytes, solid inorganic electrolytes, molten inorganic electrolytes, and the like that can be used in manufacturing lithium secondary batteries, but are not limited thereto.

[0201] Specifically, the electrolyte may include a non-aqueous organic solvent and a metal salt.

[0202] Examples of the non-aqueous organic solvent that can be used include aprotic organic solvents such as N-methyl-2-pyrrolidinone, propylene carbonate, ethylene carbonate, butylene carbonate, dimethyl carbonate, diethyl carbonate, gamma-butyrolactone, 1,2-dimethoxyethane, tetrahydrofuran, 2-methyltetrahydrofuran, dimethyl sulfoxide, 1,3-dioxolane, formamide, dimethylformamide, dioxolane, acetonitrile, nitromethane, methyl formate, methyl acetate, phosphoric acid triester, trimethoxymethane, dioxolane derivatives, sulfolane, methylsulfolane, 1,3-dimethyl-2-imidazolidinone, propylene carbonate derivatives, tetrahydrofuran derivatives, ethers, methyl propionate, and ethyl propionate.

[0203] In particular, ethylene carbonate and propylene carbonate, which are cyclic carbonates among the carbonate-based organic solvents, are preferably used since they are high-viscosity organic solvents with high dielectric constants and can dissociate lithium salts well. When such cyclic carbonates are mixed with linear carbonates having low viscosity and low dielectric constants, such as dimethyl carbonate and diethyl carbonate, in an appropriate ratio, an electrolyte having high electrical conductivity can be produced, and these carbonates can be used more preferably.

[0204] The metal salt may be a lithium salt, and the lithium salt is a substance that is easily dissolved in the non-aqueous electrolyte. For example, the anion of the lithium salt may be F - , Cl - , I - , NO3 - , N(CN)2 - , BF4 - , ClO4 - , PF6 - , (CF3)2PF4 - , (CF3)3PF3 - , (CF3)4PF2 - , (CF3)5PF- , (CF3)6P - , CF3SO3 - , CF3CF2SO3 - , (CF3SO2)2N - , (FSO2)2N - , CF3CF2(CF3)2CO - , (CF3SO2)2CH - , (SF5)3C - , (CF3SO2)3C - , CF3(CF2)7SO3 - , CF3CO2 - , CH3CO2 - , SCN - and (CF3CF2SO2)2N - One or more selected from the group consisting of:

[0205] In addition to the electrolyte components, the electrolyte may further contain one or more additives such as a haloalkylene carbonate compound such as difluoroethylene carbonate, pyridine, triethyl phosphite, triethanolamine, cyclic ether, ethylenediamine, n-glyme, hexaphosphoric acid triamide, nitrobenzene derivatives, sulfur, quinoneimine dyes, N-substituted oxazolidinones, N,N-substituted imidazolidines, ethylene glycol dialkyl ethers, ammonium salts, pyrrole, 2-methoxyethanol, or aluminum trichloride for the purposes of improving the life characteristics of the battery, suppressing a decrease in battery capacity, improving the discharge capacity of the battery, and the like.

[0206] According to an embodiment of the present invention, there is provided a battery module including the secondary battery as a unit cell, and a battery pack including the same. The battery module and the battery pack include the secondary battery having high capacity, high rate-limiting characteristics and high cycle characteristics, and therefore can be used as a power source for a medium- to large-sized device selected from the group consisting of an electric vehicle, a hybrid electric vehicle, a plug-in hybrid electric vehicle, and a power storage system. EXAMPLES

[0207] Below, preferred examples are presented to facilitate understanding of the present invention. However, the above examples are merely illustrative of the present description, and it will be apparent to those skilled in the art that various changes and modifications are possible within the scope and technical spirit of the present description. Naturally, such changes and modifications fall within the scope of the appended claims.

[0208] <Production Example> <Production of negative electrodes> Example 1: Preparation of negative electrode Preparation of the first negative electrode active material layer A first negative electrode active material layer composition was prepared by mixing silicon (average particle size (D50): 5 μm) as a silicon-based active material, a first conductive material, a second conductive material, a third conductive material, and polyacrylamide as a binder in a weight ratio of 70:9.8:10:0.2:10. The first negative electrode slurry was produced by adding the mixture to distilled water as a solvent for forming a negative electrode slurry (solid concentration: 25 wt%).

[0209] The first conductive material is carbon black C (specific surface area: 58 m 2 / g, diameter: 37 nm), and the second conductive material is plate-shaped graphite (specific surface area: 17 m 2 / g, average particle size (D50): 3.5 μm), and the third conductive material is carbon nanotubes.

[0210] The mixing method was as follows: the first conductive material, the second conductive material, the third conductive material, the binder and water were dispersed using a homomixer at 2500 rpm for 30 minutes, the active material was then added, and the mixture was dispersed at 2500 rpm for 30 minutes to prepare a slurry.

[0211] The first negative electrode slurry was applied at 2.75 mg / cm on both sides of a copper current collector (thickness: 8 μm) as a negative electrode current collector. 2 The coated layer was roll pressed and dried in a vacuum oven at 130° C. for 10 hours to form a first negative electrode active material layer (thickness: 33 μm).

[0212] Preparation of second negative electrode active material layer A second negative electrode active material layer composition was prepared by mixing SiO (average particle size (D50): 3.5 μm) as a silicon-based active material, a first conductive material, a second conductive material, and polyacrylamide as a binder in a weight ratio of 70:19.8:0.2:10. The ... slurry was produced by adding the mixture to distilled water as a solvent for forming a negative electrode slurry (solid concentration: 25% by weight).

[0213] The first conductive material is plate-shaped graphite (specific surface area: 17 m 2 / g, average particle size (D50): 3.5 μm), and the second conductive material is carbon nanotubes.

[0214] The mixing method was as follows: the first conductive material, the second conductive material, the binder and the water were dispersed using a homomixer at 2500 rpm for 30 minutes, the active material was then added, and the mixture was dispersed at 2500 rpm for 30 minutes to prepare a slurry.

[0215] The second negative electrode slurry was applied to the first negative electrode active material layer at a concentration of 1 mg / cm. 2 The coated layer was rolled and dried in a vacuum oven at 130° C. for 10 hours to form a second negative electrode active material layer (thickness: 15 μm).

[0216] Thereafter, lithium metal was transferred onto the second negative electrode active material layer to carry out prelithiation.

[0217] The values ​​of Formula 1 and the dosage of pre-lithiation in Example 1 are as shown in Table 1 below. Except for changing Formula 1 and the dosage of pre-lithiation in Table 1 below, negative electrodes of Examples 2, 3, and Comparative Examples 1 to 3 were prepared.

[0218] [Table 1]

[0219] Incidentally, the pre-lithiation amount in the examples and comparative examples can be calculated according to the following formula A'. [Formula A'] Pre-lithiated lithium capacity / negative electrode filling capacity (first negative electrode active material layer + second negative electrode active material layer)

[0220] Whether or not the lithiation has reached a degree that satisfies the range of the above formula 1 in the Examples and Comparative Examples can be confirmed by the following method.

[0221] 1) Proceed with pre-lithiation of the negative electrode, and combine with a coin half cell to proceed with lithiation. 2) Charge / discharge at 0.1C CC / CV 5mV, 0.005C cut off, delithiation: 0.1C 1.0V CC, and compare whether (initial (pristine) charge capacity - pre-lithiation electrode charge capacity) = equals the lithium capacity after lithiation has progressed. 3) Check the amount of lithium loss when pre-lithiation has progressed by calculating (initial charge capacity - pre-lithiation electrode charge capacity) / initial charge capacity*100 = lithiation amount (%).

[0222] Example 4: Preparation of negative electrode Preparation of the first negative electrode active material layer A first negative electrode active material layer was produced in the same manner as in Example 1.

[0223] Preparation of second negative electrode active material layer The second negative electrode slurry was prepared in the same manner as in Example 1, except that SiO (average particle size (D50): 3.5 μm) as a silicon-based active material, artificial graphite as a carbon-based active material, a first conductive material, a second conductive material, and polyacrylamide as a binder were added in a weight ratio of 30:50:5:5:10 to distilled water as a solvent for forming a negative electrode slurry (solid concentration: 25 wt %).

[0224] The first conductive material is carbon black C (specific surface area: 58 m 2 / g, diameter: 37 nm), and the second conductive material is plate-shaped graphite (specific surface area: 17 m 2 / g, average particle size (D50): 3.5 μm.

[0225] Thereafter, lithium metal was transferred onto the second negative electrode active material layer to carry out pre-lithiation, whereby Equation 1 satisfied 1.8, and the pre-lithiation amount satisfied 19.1%.

[0226] Example 5: Preparation of negative electrode In the preparation of the second negative electrode active material layer of Example 1, a composition for the second negative electrode active material layer was prepared using SiC (average particle size (D50): 3.5 μm) as a silicon-based active material, a first conductive material, a second conductive material, and polyacrylamide as a binder in a weight ratio of 70:19.8:0.2:10, and the composition was added to distilled water as a solvent for forming a negative electrode slurry to prepare a second negative electrode slurry. The negative electrode was prepared under the same conditions as in Example 1 (solid concentration: 25 wt %). At this time, Equation 1 satisfied 1.6, and the amount of pre-lithiation satisfied 16.48%.

[0227] Example 6: Preparation of negative electrode Preparation of the first negative electrode active material layer A first negative electrode active material layer was produced in the same manner as in Example 1.

[0228] Preparation of second negative electrode active material layer A second negative electrode active material layer composition was prepared in a weight ratio of 50:20:10:10:10:10 using SiO (average particle size (D50): 3.5 μm) as a silicon-based active material, artificial graphite, a first conductive material, a second conductive material, and polyacrylamide as a binder in Example 1. The composition was prepared in the same manner as in Example 1, except that the second negative electrode slurry was prepared (solid concentration: 25 wt %) by adding distilled water as a solvent for forming a negative electrode slurry.

[0229] The first conductive material is plate-shaped graphite (specific surface area: 17 m 2 / g, average particle size (D50): 3.5 μm), and the second conductive material is carbon nanotubes.

[0230] Thereafter, lithium metal was transferred onto the upper portion of the second negative electrode active material layer to proceed with pre-lithiation. At this time, Equation 1 satisfied 1.5, and the pre-lithiation amount satisfied 15.74%.

[0231] Comparative Example 4: Production of negative electrode An active material layer composition was prepared by mixing silicon-based active material Si (average particle size (D50): 5 μm), a first conductive material, and polyacrylamide as a binder in a weight ratio of 70:20:10. A negative electrode slurry was prepared by adding the mixture to distilled water as a solvent for forming a negative electrode slurry (solid concentration 25 wt%).

[0232] The first conductive material is carbon black C (specific surface area: 58 m 2 / g, diameter: 37 nm) is used.

[0233] As for the mixing method, the first conductive material, binder and water were dispersed using a homomixer at 2500 rpm for 30 minutes, and then the active material was added, followed by dispersion at 2500 rpm for 30 minutes to prepare a slurry.

[0234] The negative electrode current collector was a copper current collector (thickness: 8 μm) on both sides of which the negative electrode slurry was applied at 85 mg / 25 cm. 2 The coated layer was roll pressed and dried in a vacuum oven at 130° C. for 10 hours to form a negative electrode active material layer (thickness: 33 μm).

[0235] Thereafter, lithium metal was transferred onto the upper portion of the negative electrode active material layer to proceed with pre-lithiation. At this time, formula 1 satisfied 1.6, and the pre-lithiation amount satisfied 17.28%.

[0236] Comparative Example 5: Production of negative electrode A negative electrode was manufactured in the same manner as in Example 1, except that the stacking order of the first negative electrode active material layer and the second negative electrode active material layer was changed. In this case, Equation 1 satisfied 1.6, and the pre-lithiation amount satisfied 17.28%.

[0237] Comparative Example 6: Production of negative electrode An active material layer composition was prepared by mixing Si (average particle size (D50): 5 μm), SiO (average particle size (D50): 3.5 μm), a first conductive material, a second conductive material, a third conductive material, and polyacrylamide as a binder in a weight ratio of 52.5:17.5:9.8:10:0.2:10. The negative electrode slurry was prepared by adding the mixture to distilled water as a solvent for forming the negative electrode slurry (solid concentration 25 wt%).

[0238] The first conductive material is carbon black C (specific surface area: 58 m 2 / g, diameter: 37 nm), and the second conductive material is plate-shaped graphite (specific surface area: 17 m 2 / g, average particle size (D50): 3.5 μm), and the third conductive material is carbon nanotubes.

[0239] The mixing method was as follows: the first conductive material, the second conductive material, the third conductive material, the binder and the water were dispersed using a homomixer at 2500 rpm for 30 minutes, the active material was then added, and the mixture was dispersed at 2500 rpm for 30 minutes to prepare a slurry.

[0240] The negative electrode current collector was a copper current collector (thickness: 8 μm) on both sides of which the negative electrode slurry was applied at 85 mg / 25 cm. 2 The coated layer was roll pressed and dried in a vacuum oven at 130° C. for 10 hours to form a negative electrode active material layer (thickness: 33 μm).

[0241] Thereafter, lithium metal was transferred onto the upper portion of the negative electrode active material layer to proceed with pre-lithiation. At this time, formula 1 satisfied 1.6, and the pre-lithiation amount satisfied 14.8%.

[0242] <Secondary battery manufacturing> LiNi as the positive electrode active material 0.6 Co 0.2 Mn 0.2O2 (average particle size (D50): 15 μm), carbon black (product name: Super C65, manufacturer: Timcal) as a conductive material, and polyvinylidene fluoride (PVdF) as a binder were added in a weight ratio of 97:1.5:1.5 to N-methyl-2-pyrrolidone (NMP) as a solvent for forming a positive electrode slurry to prepare a positive electrode slurry (solid concentration 78 wt%).

[0243] The positive electrode current collector was an aluminum current collector (thickness: 12 μm) and the positive electrode slurry was applied to both sides at 537 mg / 25 cm. 2 The coated layer was rolled and dried in a vacuum oven at 130° C. for 10 hours to form a positive electrode active material layer (thickness: 65 μm) to prepare a positive electrode (thickness of positive electrode: 77 μm, porosity: 26%).

[0244] An electrolyte was injected between the positive electrode and the negative electrode of each of the examples and comparative examples via a polyethylene separator to prepare a lithium secondary battery.

[0245] The electrolyte was an organic solvent made by mixing fluoroethylene carbonate (FEC) and diethyl carbonate (DMC) in a volume ratio of 30:70, to which vinylene carbonate was added at 3 wt% based on the total weight of the electrolyte, and LiPF6 was added as a lithium salt at a concentration of 1M.

[0246] Experimental example 1: Life characteristic evaluation The secondary batteries including the negative electrodes manufactured in Examples 1 to 6 and Comparative Examples 1 to 6 were subjected to a life evaluation using an electrochemical charger / discharger to evaluate the capacity retention rate. The secondary batteries were subjected to an in-situ cycle test at 4.2-3.0V 1C / 0.5C, and during the test, the batteries were charged / discharged at 0.33C / 0.33C (4.2-3.0V) every 50 cycles to measure the capacity retention rate. The RPT capacity retention rates are shown in Table 2 below. Capacity retention rate (%) = {(discharge capacity at Nth cycle) / (discharge capacity at first cycle)} X100

[0247] FIG. 2 is a graph showing the RPT capacity maintenance rate according to the examples and the comparative examples.

[0248] Experimental example 2: Resistance increase rate measurement evaluation In the test of the above-mentioned Experimental Example 1, the capacity retention rate was measured by charging / discharging at 0.33C / 0.33C (4.2-3.0V) every 50 cycles, and then the resistance was measured by discharging at 2.5C pulse at SOC50, and the resistance increase rate was compared and analyzed.

[0249] 3 shows a graph of the RPT resistance increase rate according to the embodiment and the comparative example. Specifically, it means a graph of the RPT resistance increase rate (measured with 2.5C pulse in the discharge direction at SOC50 after 0.33C / 0.33C, 4.2-3.0V charge / discharge every 50 cycles during in-situ continuous cycle test) according to the embodiment and the comparative example.

[0250] Furthermore, data at 200 cycles was calculated for each of the life characteristic evaluation and the resistance increase rate measurement evaluation, and the results are shown in Table 2 below.

[0251] [Table 2]

[0252] In the negative electrode for a lithium secondary battery according to the present application, the capacity of lithium provided by pre-lithiation with respect to the discharge capacity of the second active material layer containing a silicon-based active material is adjusted to the range of formula 1. As can be seen from Table 2, it has a first negative electrode active material layer composition having high capacity characteristics, and at the same time, a second negative electrode active material layer composition is included to solve the life characteristics, and the usage ratio of the silicon-based active material during initial charging and discharging is limited, and the role of a reservoir is given, thereby optimizing the capacity characteristics and life characteristics, and it has been confirmed that excellent effects can be obtained. Comparative Example 1 and Comparative Example 2 correspond to the case where the range of formula 1 according to the present application is exceeded or is less than that, and Comparative Example 3 corresponds to the case where pre-lithiation was not performed. It should be noted that the comparative example 4 satisfies the range of formula 1, but corresponds to a single-layer negative electrode having 100% pure Si, the comparative example 5 satisfies the range of formula 1, but differs from Example 1 in that the order of the first and second layers is changed, and the comparative example 6 satisfies the range of formula 1, but corresponds to a single layer having a mixed active material layer of Si and SiO.

[0253] As can be seen from Table 2 above, in the cases of Comparative Examples 1 to 6, the capacity retention rate is inferior to that in the cases of Examples 1 to 6, and the resistance increase rate is also high.

[0254] In other words, it was confirmed through the data of the examples and comparative examples that the present invention is characterized by a double-layered anode using first and second anode active material layers to improve life characteristics and capacity characteristics, and further characterized by optimizing the pre-lithiation ratio to maximize life characteristics. [Explanation of symbols]

[0255] 10...Second negative electrode active material layer 20...first negative electrode active material layer 30 Negative electrode current collector layer

Claims

1. A negative electrode for a lithium secondary battery, comprising: a negative electrode current collector layer; a first negative electrode active material layer provided on one or both sides of the negative electrode current collector layer; and a second negative electrode active material layer provided on a surface of the first negative electrode active material layer opposite to a surface in contact with the negative electrode current collector layer, the first negative electrode active material layer includes a first negative electrode active material layer composition including a first negative electrode active material, and the second negative electrode active material layer includes a second negative electrode active material layer composition including a second negative electrode active material, The first negative electrode active material includes 95 parts by weight or more of SiOx (x=0) based on 100 parts by weight of the first negative electrode active material, The second negative electrode active material may include one or a mixture of two or more selected from the group consisting of a carbon-based active material, a silicon-based active material, a metal-based active material capable of forming an alloy with lithium, and a lithium-containing nitride; The silicon-based active material is at least one selected from the group consisting of SiOx (0<x<2), SiC, and a Si alloy; the silicon-based active material is 1 part by weight or more and 100 parts by weight or less based on 100 parts by weight of the second negative electrode active material, The second negative electrode active material layer satisfies the following formula 1: [Formula 1] 0.5≦B / A≦2 In the above formula 1, A is the discharge capacity of the second negative electrode active material layer, B means the capacity of pre-lithiation lithium.

2. 2. The negative electrode for a lithium secondary battery according to claim 1, wherein the silicon-based active material comprises SiOx (0<x<2).

3. The negative electrode of claim 1 , wherein the first negative electrode active material is 60 parts by weight or more based on 100 parts by weight of the first negative electrode active material layer composition.

4. The thickness of the first negative electrode active material layer is 10 μm or more and 200 μm or less, 2 . The negative electrode for a lithium secondary battery according to claim 1 , wherein the second negative electrode active material layer has a thickness of 10 μm or more and 100 μm or less.

5. 2 . The negative electrode for a lithium secondary battery according to claim 1 , wherein the weight loading amount (a) of the first negative electrode active material layer composition is 1.5 times or more the weight loading amount (b) of the second negative electrode active material layer composition.

6. the first negative electrode active material layer composition further includes at least one selected from the group consisting of a first negative electrode conductive material; and a first negative electrode binder; 2. The negative electrode for a lithium secondary battery according to claim 1, wherein the second negative electrode active material layer composition further comprises at least one selected from the group consisting of a second negative electrode conductive material; and a second negative electrode binder.

7. 7. The negative electrode for a lithium secondary battery according to claim 6, wherein the first negative electrode conductive material and the second negative electrode conductive material include at least one selected from the group consisting of a dot-like conductive material; a linear conductive material; and a sheet-like conductive material.

8. Providing a negative electrode current collector layer; applying a first negative electrode active material layer composition to one or both surfaces of the negative electrode current collector layer to form a first negative electrode active material layer; and forming a second negative electrode active material layer on a surface of the first negative electrode active material layer opposite to a surface of the first negative electrode active material layer that is in contact with the negative electrode current collector layer, The first negative electrode active material includes 95 parts by weight or more of SiOx (x=0) based on 100 parts by weight of the first negative electrode active material, The second negative electrode active material may include one or a mixture of two or more selected from the group consisting of a carbon-based active material, a silicon-based active material, a metal-based active material capable of forming an alloy with lithium, and a lithium-containing nitride; The silicon-based active material is at least one selected from the group consisting of SiOx (0<x<2), SiC, and a Si alloy; the silicon-based active material is 1 part by weight or more and 100 parts by weight or less based on 100 parts by weight of the second negative electrode active material, The second negative electrode active material layer satisfies the following formula 1: [Formula 1] 0.5≦B / A≦2 In the above formula 1, A is the discharge capacity of the second negative electrode active material layer, B means the capacity of pre-lithiation lithium.

9. pre-lithiating the negative electrode having the first negative electrode active material layer and the second negative electrode active material layer formed on the negative electrode current collector layer; 10. The method of claim 8, wherein the prelithiation of the negative electrode comprises a lithium electrolytic plating process; a lithium metal transfer process; a lithium metal deposition process; or a stabilized lithium metal powder (SLMP) coating process.

10. Positive electrode; The negative electrode for a lithium secondary battery according to any one of claims 1 to 7; A separator disposed between the positive electrode and the negative electrode; and an electrolyte.

Citation Information

Patent Citations

  • Negative electrode and battery using it

    JP2004171874A

  • Anode for lithium ion battery

    JP2009080971A

  • All-solid battery

    JP2019160407A

  • Electrode for lithium ion secondary battery and lithium ion secondary battery

    JP2020140896A

  • Lithium secondary battery and its manufacturing method

    JP2020525989A